Renovascular hypertension from the BCR‐ABL tyrosine kinase inhibitor ponatinib - Amin, Syed O. (J Clin Hypertens (Greenwich), 2020)
Drug‐induced hypertension is one of the commonest causes of secondary hypertension. In the last few years, secondary hypertension due to tyrosine kinase inhibitors, from the vascular endothelial growth factor class, has been recognized to be an important cause of hypertension, as well as proteinuria, and occasionally kidney dysfunction in some cases. Less well‐recognized is that BCR‐ABL tyrosine kinase inhibitors also have adverse vascular effects. These manifest as vascular stenoses in large vessels, which may sometimes cause renal artery stenosis and subsequent hypertension. We describe a case report which presented as classical bilateral renal artery stenosis, and responded to revascularization. Increased awareness of these effects, as well as research into the pathogenesis, may provide more insight into vascular biology.